Arm and leg power output in swimmers during simulated swimming - Swaine, I. L. (Medicine & Science in Sports & Exercise, 2000)
Purpose: Previously, it has not been possible to compare power output of the arms and legs during simulated swimming using dry-land ergometry. The purpose of this study was to determine arm-pulling and leg-kicking power using isokinetic dry-land ergometry. Methods: Twenty-two highly trained male swimmers of mean (± SD) age, 23 ± 3.6 yr; body mass, 78 ± 5.9 kg; and stature, 1.79 ± 0.04 m were recruited to the study. First, subjects performed 10 s of all-out exercise at each of five resistance settings, with 1 h rest in between, to determine the best maximal pull velocity (MPVopt). Second, they performed an all-out 30-s test at MPVopt, which was repeated the following day. These repeated 30-s tests were performed separately using simulated front-crawl arm-pulling and leg-kicking, on a computer-interfaced swim bench and purpose-built leg-kicking ergometer. Peak and mean power output (PPO; MPO) were determined from regression analysis of the power vs time relationship. Results: The mean (± SEM) PPO for arms and legs were 304 ± 22 W versus 435 ± 36 W. For MPO, the means were 225 ± 31 W vs 312 ± 26 W, respectively. These values were attained at mean MPVopt of 2.5 ± 0.2 m·s-1 for arms and 2.3 ± 0.4 m·s-1 for legs. The variation in PPO from repeated testing was 7.3% for arms and 8.3% for legs. Conclusions: These results show that the legs can sustain greater power output than the arms during simulated swimming. Also, the intra-subject variation in measurement of power output is small using these dry-land ergometers. These methods of assessment might be useful in explaining swimming performance and in monitoring changes that take place during training.